1995
DOI: 10.1046/j.1469-0705.1995.06020140.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study on fetal weight estimation using limb circumferences obtained by three‐dimensional ultrasound

Abstract: The aim of this prospective study was to evaluate the usefulness of fetal weight estimation in a prospective study, based on formulae derived from a previous retrospective study, using forward stepwise multiple regression analysis. Three-dimensional ultrasound was used to make reproducible measurement of limb circumferences, which formed the basis of our models. A total of 213 women with singleton pregnancies were scanned in the week prior to delivery and the following variables were measured: biparietal diame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
4

Year Published

2001
2001
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 0 publications
2
22
0
4
Order By: Relevance
“…Several studies have demonstrated that fetal thigh and upper-arm volumes are better predictors of fetal weight than conventional 2-D measurements 111118. A multivariable approach that incorporates other maternal and fetal characteristics may further improve the estimation 119120.…”
Section: Improving Accuracy Of Estimated Fetal Weight By Ultrasonomentioning
confidence: 99%
“…Several studies have demonstrated that fetal thigh and upper-arm volumes are better predictors of fetal weight than conventional 2-D measurements 111118. A multivariable approach that incorporates other maternal and fetal characteristics may further improve the estimation 119120.…”
Section: Improving Accuracy Of Estimated Fetal Weight By Ultrasonomentioning
confidence: 99%
“…[42][43][44] Another parameter, ArmC, can be very difficult to measure in a reproducible manner if the examiner does not precisely use the middle of the humeral diaphysis. Favre and coworkers 45,46 have solved this problem by using 3-dimensional multiplanar views to standardize the arm circumference measurement at the midpoint of the humeral shaft. Others have used 3-dimensional sonography to measure fetal arm volume for birth WT prediction and to evaluate intrauterine growth.…”
mentioning
confidence: 92%
“…The accuracy of Hadlock formula is variable among researchers. Its mean percentage error ranged from À9.1% to À14.2%, whereas the random error ranged from 7% to 11.9% [5,16,17]. These variations are higher for macrosomic and low birth weight fetuses, where there is a tendency for under-estimation and over-estimation of the birth weights, respectively [5,17].…”
Section: Discussionmentioning
confidence: 99%